Buharism and Tinubuism: A Religio-Political Analysis of Nigerian Democratization from 2015 to the Present (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This article analyzes the impact of Buharism and Tinubuism on Nigeria's democracy, emphasizing the effect of politico-cultural and religious dominance by central southern and northern elites on governance, citizenship, rights for individuals, and equality. It examines the governing class's political, religious, and physical endeavors from 2015 to the present and their ramifications on the current status quo. The research employs primary and secondary sources to elucidate the political-religious nature of developments and their effects on state and national politics. The paper reveals the importance of ethnic and religious elements in Nigerian democracy, especially in the southern and northern areas, where religious disparities profoundly affect advancement, democratic systems, patronage, and state security.